Few‐Layered Tin Sulfide Nanosheets Supported on Reduced Graphene Oxide as a High‐Performance Anode for Potassium‐Ion Batteries. Issue 10 (5th February 2019) - Fang, Lingzhe; Xu, Jing; Sun, Shuo; Lin, Baowei; Guo, Qiubo; Luo, Da; Xia, Hui
Abstract: Anodes involving conversion and alloying reaction mechanisms are attractive for potassium‐ion batteries (PIBs) due to their high theoretical capacities. However, serious volume change and metal aggregation upon potassiation/depotassiation usually cause poor electrochemical performance. Herein, few‐layered SnS2 nanosheets supported on reduced graphene oxide (SnS2 @rGO) are fabricated and investigated as anode material for PIBs, showing high specific capacity (448 mAh g −1 at 0.05 A g −1 ), high rate capability (247 mAh g −1 at 1 A g −1 ), and improved cycle performance (73% capacity retention after 300 cycles). In this composite electrode, SnS2 nanosheets undergo sequential conversion (SnS2 to Sn) and alloying (Sn to K4 Sn23, KSn) reactions during potassiation/depotassiation, giving rise to a high specific capacity. Meanwhile, the hybrid ultrathin nanosheets enable fast K storage kinetics and excellent structure integrity because of fast electron/ionic transportation, surface capacitive‐dominated charge storage mechanism, and effective accommodation for volume variation. This work demonstrates that K storage performance of alloy and conversion‐based anodes can be remarkably promoted by subtle structure engineering. Abstract : Few‐layered SnS2 nanosheets vertically alligned on reduced graphene oxide nanosheets are demonstrated as high‐performance anode material for potassium‐ion batteries. Besides the high specific capacities based on sequential conversion and alloying reactions, excellent rate capability and cycling stability are also achieved by enhanced surface charge storage, fast electron/ionic transportation, and improved structural stability, benifiting from the subtle structure engineering.